Book Review H.K. Chang: Civilizations of the Silk Road - Bahauddin, Bahauddin (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2024)
Through this book, Chang skillfully portrays the interactions among various civilizations and societies along the Silk Road from 500 BC to 1500 AD. Using primary data in the form of paintings, artifacts, and maps, the book weaves together the cultural exchanges that stretched across the Silk Road, starting with the pioneering success of Zhang Qian, who initiated the opening of the Silk Road, and tracing the origins and spread of religions such as Zoroastrianism, Buddhism, Christianity, Manichaeism, Nestorian Christianity, and Islam. The book also elegantly describes the historically significant migrations of various peoples from east to west, including the Xiongnu, Yuezhi, Han, Qiang, Hephthalites, Turkic groups, Uighurs, Mongols, and Xibe.